A proposal of a fecal scoring system based on physicochemical analyses of suckling pig feces - Ana Maria Pons; Blanca González; Joan Pujols; Jordi Serratosa; Joaquim Segalés; Ernesto A. Gómez; Jorge Martínez (Porcine Health Management)
Abstract Background Digestive disorders are one of the main health problems in suckling piglets. The correct visual identification of feces in suckling piglets is an important tool for the diagnosis of enteric diseases. The aim of the present observational study was to analyze different physicochemical parameters of the feces of suckling piglets aged 0 to 21 days: visual appearance (color and consistency), fecal dry matter (FDM) content and pH. A total of 482 fecal samples were collected and visually classified into six categories: meconium, colostrum stage feces and 4 further scores according to the degree of consistency: 0 = form; 1 = pasty; 2 = liquid; and 3 = watery feces. The percentage of FDM was estimated by two drying methods, oven and microwave, doing duplicates in each one to evaluate methods, and both were compared. Results The most frequent colors of each feces category were dark green or dark brown for meconium; orange for colostrum; formed feces were mostly ocher and for the rest of the feces, the colors varied predominantly cream and ocher. Regarding FDM, liquid and watery categories had no statistically significant differences between them; meconium and colostrum feces FDM were not statistically different from pasty feces. The correlation coefficient between the FDM values of the duplicate analyses of the samples by both methods (oven and microwave) was very high (> 0.988). Importantly, no differences were found while comparing the results between both methods (p = 0.078), and the correlation coefficient between all samples analyzed with both methods was very high (> 0.98). Meconium was the only one that differed significantly from the rest in terms of pH. Conclusion The physicochemical study of the feces of suckling piglets including color, FDM and pH allowed the establishment of an objective fecal score to characterize the stools in this age group.